Morality and Justice : Reading Boylan's 'A Just Society' - Gordon, John-Stewart, 1976- (Lexington Books, 2009)
The essays in this book engage the original and controversial claims from Michael Boylan's A Just Society. Each essay discusses Boylan's claims from a particular chapter and offers a critical analysis of these claims. Boylan responds to the essays in his lengthy and philosophically rich reply.